PERAN HUKUM ADAT DALAM PELESTARIAN LINGKUNGAN HIDUP DAERAH - Sirtha, I Nyoman (Bumi Lestari; Vol 3 No 2, 2012)
A traditional law (Adat Law) is one element on construction The Unwritten National Law of Indonesia. On sustainable development which deals with environmental dimention in the regional frame and in line with the spirit of regional otonomy which implys exploitate (utilize) the natural resources and biological potencies includes norms which is still practise by the society for the human’s wealth and other creatures. Therefore, Adat Law which is till existing among the societies can play an important role to regulate and to constrain the human behaviors in term of environmental conservation in order to realize the harmonious and equal life
Keywords: adat law, environment, resource, sustainable